Werk maken van werk voor allochtonen : eindrapport - Verhoeven, Hans; Van Roy, E.; Lamberts, M.; Martens, Albert (Leuven: KUL. Departement Sociologie, 2001)
"Onderzoek kadert in het VIONA-arbeidsmarktprogramma 1998"